Pengaruh Media e-Flipbook dengan Pendampingan Orang Tua terhadap Perkembangan Bahasa Anak Kelompok B di TK Islam Darul Yaqin Kecamatan Kediri - Haeva Nasiun; Fahruddin; Muslihatun Maulidian; Aulia Dwi Amalina Wahab (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Early childhood is a golden age that plays a crucial role in determining the development of children’s basic abilities, particularly language skills, which are essential for communication and social interaction. This study aimed to examine the effect of e-flipbook media accompanied by parental involvement on the language development of Group B children at TK Islam Darul Yaqin, Kediri District. This study employed a quantitative approach with an experimental research method using a one-group pretest–posttest design. The population of this study consisted of all children enrolled at TK Islam Darul Yaqin, totaling 37 children. The sampling technique used was purposive sampling, in which all 18 children in Group B were selected as the research sample. Data were collected through observation and documentation. Data analysis was conducted by first performing a normality test as a prerequisite for analysis, followed by hypothesis testing using a paired sample t-test with the assistance of IBM SPSS version 31 for Windows. The results showed that the average language development score before treatment (pretest) was 45.89, which fell into the category of Beginning to Develop (BD). After the implementation of the e-flipbook media accompanied by parental involvement, the posttest results indicated an increase in the average language development score to 93.89, which was categorized as Very Well Developed (VWD). The hypothesis testing results showed a significance value (2-tailed) of 0.01, which was lower than 0.05; therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Thus, it can be concluded that the use of e-flipbook media accompanied by parental involvement has a significant effect on the language development of Group B children at TK Islam Darul Yaqin, Kediri District.